On Strong and Weak Sustainability, with an Application to Self-Susp ending Real-Time Tasks - Cerqueira, Felipe (2018)
Motivated by an apparent contradiction regarding whether certain scheduling policies are sustainable, we revisit the topic of sustainability in real-time scheduling and argue that the existing definitions of sustainability should be further clarified and generalized. After proposing a formal, generic sustainability theory, we relax the existing notion of (strongly) sustainable scheduling policy to provide a new classification called weak sustainability. Proving weak sustainability properties allows reducing the number of variables that must be considered in the search of a worst-case schedule, and hence enables more efficient schedulability analyses and testing regimes even for policies that are not (strongly) sustainable. As a proof of concept, and to better understand a model for which many mistakes were found in the literature, we study weak sustainability in the context of dynamic self-suspending tasks, where we formalize a generic suspension model using the Coq proof assistant and provide a machine-checked proof that any JLFP scheduling policy is weakly sustainable with respect to job costs and variable suspension times.